PENGARUH JENIS LIMBAH TERHADAP BOBOT LARVA PADA BIOKONVERSI LIMBAH PASAR MENGGUNAKAN LARVA Hermetia illucens (BLACK SOLDIER FLY) - Yulanda Nur Rojabi; Edi Hernawan; Rinaldi Rizal Putra (Universitas Lambung Mangkurat, 2021)
The market waste is solid waste organic consist of set of many vegetable which are not feasible for sale. The market waste in general predominated by mustard greens, cabbage, tomato, and chayote. One of the market waste treatment using the bioconversion process of the Hermetia illucens larvae (Black Soldier Fly) or commonly called Maggot. The research was conducted to investigate the effect of the type of waste on larvae weights in the bioconversion of market waste using Hermetia illucens larvae (Black Soldier Fly). The research was carried out in september 2020. The research method use was true-experiment. The sample use was 200 Hermetia illucens larvae/treatments taken from the population by technique simple random sampling. The experiment was conducted for 12 days. Samples were taken periodically to be analyzed for their weight, supported by substrate consumption, waste reduction index, survival rates. Based on the results of the study can be concluced that there is giving the mixed mustard greens and cabbage waste produces the largest larvae weight with feed rate 60 mg/larvae/day or average weight of 92,20 grams. At this condition, the optimal waste reduction in the bioconversion process was observed as substrate consumption of 96,80% and waste reduction index of 33,61% obtained in the waste feed media of the mixed mustard greens and cabbage.While the survival rate of 99,90% obtained in the waste media of the mixed mustard greens and chayote with feed rate 60 mg/larvae/day.